Necessity of an agriculture-based curriculum in Bangladesh: A pathway for sustainable economic growth (Journal of Bangladesh Academy of Sciences, 2025)
The findings of this study highlight a significant gap in the current educational curriculum regarding agricultural relevance and practical skill development. Most respondents—comprising both students and educators—strongly preferred integrating agriculture-focused subjects, especially  in  rural  settings  where  farming  remains  central  to livelihoods.  Participants  believe  early  exposure  to  agricultural education and hands-on practical experience can empower students with real-world skills, reduce rural-urban migration, and support local economic growth. Additionally, an agriculture-based curriculum has the potential to address key challenges such as youth unemployme nt, food insecurity, and environmental degradation. Such a curriculum could promote long-term ecological balance and economic resilience by  fostering  awareness  and  competence  in  sustainable  agricultural practices.  Therefore,  incorporating  agriculture  into  mainstream education is not merely an academic enhancement but a strategic move toward sustainable national economic development.J. Bangladesh Acad. Sci. 49(1); 113-121: June 2025